Color evolution of a pyrrole-based enone dye in radical photopolymerization formulations. (April 2021) - Xue, Tanlong; Tang, Liqun; Tang, Ruifen; Li, Yang; Nie, Jun; Zhu, Xiaoqun
Abstract: Dyes bearing vinyl expanded ketone core have been widely used as photointiator/sensitizer in visible light induced polymerization. However, little attention was paid to the color evolution of these dyes in photopolymerization formulation. In this work, a pyrrole-based ketone derivative (C3PY) was synthesized and characterized, which displays maximum absorption wavelength at 414 nm. Under 405 nm LED lamp, C3PY itself can initiate the radical polymerization of acrylates, during which significant photo-bleaching were observed and colorless polymer could be obtained. Addition of triethanolamine (TEOA) improved the monomer conversion. Very contrast, when combined with iodonium salt (ONI), C3PY/ONI resulted in deep colored acrylate polymer. Steady state photolysis experiments, NMR spectroscopy, and DFT/TDDFT calculations were performed to study the chromatic mechanism of C3PY in various formulation. Accordingly, some compounds were discreetly deduced to be responsible for the deep color in acrylate polymer. This work provided first investigation on the color change of pyrrole-based ketone dye in radical photopolymerization formulation, which may helpful to understand others dye's chromatic behaviors in radical photopolymerization. Graphical abstract: Image 1 Highlights: Color evolution of a pyrrole-based ketone dye (C3PY) in radical photopolymerization formulation were illustrated. Using amine as additive, clear and transparent photopolymer could be obtained. When C3PY was used to sensitize ONI, red to blue photopolymer were formed. Protonic acid released by C3PY/ONI, and C3PY dimer formation were responsible to the color in obtained photopolymer.